Complexo de refugiados em DADAAB : estado de exceção em caráter permanente? - Trivellato, Márcia Carolina Santos (2019)
The present research aims to analyze whether the extension of the existence of the refugee camps in Dadaab constitutes a permanent state of exception, using the theoretical contribution of the birth-nation nexus of Hannah Arendt and the biopolitics of Giorgio Agamben. In order to be possible its development, the work is divided into three specific objectives detailed below. First, it will be studied the rupture of the birth-nation nexus in Arendt, given that the traditional criteria of birth in the territory or by blood, adopted by the contemporary nation-state, are not sufficient to encompass all individuals in the category of citizen. As a consequence, minorities - embodied in the figure of the refugees in this work - are at the same time excluded and included of the discretion of sovereign power through the institute of the state of exception, described by Agamben as a political-legal device used in strategic situations of power and characterized by the temporary suspension of the normative order by determination of the hidden power of the sovereign. In addition, a historical-conceptual approach is taken on the “humanitarian crisis” of refugees and refugee camps, as well as the lack of legal and legal protection of these environments, despite the great amount of legislation produced on the subject, which allows the production of naked lives in the ideological and physical fields. Finally, it is shown that the extension of the existence of refugee camps in Dadaab establishes a physical and permanent state of exception, in view of the repeated extensions of its existence. Therefore, the hypothesis of the study is based on the idea that the extension of the existence of refugee camps in Dadaab, measure designed to be merely palliative, proves the rupture of the birth-nation nexus denounced by Hannah Arendt in establishing a state of exception as described by Agamben, of permanent character. As for the methodology, the present work is developed from the case study of the refugee complex in Dadaab and uses the quantitative and qualitative method through secondary data. In addition, bibliographic and documentary procedures are adopted, which will accompany all stages of research development.